HASAN AL-SAQAF'S CRITICISM ON THE ASSESSMENT OF THE PROPHET'S HADITH BY NASHIRUDDIN AL-ALBANI IN THE BOOK OF TANAQUDHAT AL-ALBANI AL-WADIHAT - Putri, Rizki; Siska Sukmawati (al Dhikra | Jurnal Studi Qur'an dan Hadis, 2024)
This study aims to analyze the assessment of the hadith of the prophet by Nashiruddin Al-Albani in one of the hadith books of a contemporary Jordanian scholar named Hassan bin Ali Assaqaf. This research method is library research with a qualitative method that is organized descriptively, comparatively, and analytically. The book of Tanaqudhat al-Albani al-Wadihat by Hasan bin Ali Assaqaf is a book that contains corrections to Nashiruddin al-Albani's mistakes in assessing the Prophetic traditions. The inconsistencies made by al-Albani made Hasan bin Ali Assaqaf examine his works to find out more about the mistakes made by al-Albani. Shaykh al-Albani is a Muslim scholar who devotes all his abilities in researching the Prophetic traditions. However, al-Albani's efforts were countered by Hasan b. 'Ali Assaqaf because of al-Albani's errors and inconsistencies in assessing hadith, as well as his attitude of not following the previous scholars of hadith who prioritized faith over ijtihad